2021
DOI: 10.1038/s41467-021-24813-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic enhancers drive esophageal squamous cell carcinogenesis and metastasis

Abstract: The role of cis-elements and their aberrations remains unclear in esophageal squamous cell carcinoma (ESCC, further abbreviated EC). Here we survey 28 H3K27ac-marked active enhancer profiles and 50 transcriptomes in primary EC, metastatic lymph node cancer (LNC), and adjacent normal (Nor) esophageal tissues. Thousands of gained or lost enhancers and hundreds of altered putative super-enhancers are identified in EC and LNC samples respectively relative to Nor, with a large number of common gained or lost enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…At the mechanistic level, SEs inhibition hinders the transcription of stemness and pro-metastatic genes [ 94 ]. Another advanced study identified a plethora of SEs assembled in esophageal squamous cell carcinoma (ESCC) and metastatic lymph node cancer (LNC) cells [ 95 ]. Based on H3K27ac profiling, SEs signatures were precisely defined in primary and lymph node tumors.…”
Section: Dna Grammar and Syntax Features And Epigenetic Characteristi...mentioning
confidence: 99%
“…At the mechanistic level, SEs inhibition hinders the transcription of stemness and pro-metastatic genes [ 94 ]. Another advanced study identified a plethora of SEs assembled in esophageal squamous cell carcinoma (ESCC) and metastatic lymph node cancer (LNC) cells [ 95 ]. Based on H3K27ac profiling, SEs signatures were precisely defined in primary and lymph node tumors.…”
Section: Dna Grammar and Syntax Features And Epigenetic Characteristi...mentioning
confidence: 99%
“…There are two major subtypes of Esophageal cancer (EC), esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) ( Ye et al, 2021 ). In China, more than 90% of esophageal cancer cases are ESCC ( Zhang X. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SEs can be acquired by cancer cells at key oncogenes, 9,11 and over 60% of SEs are tissue‐ or cancer‐type‐specific 9,12 . Furthermore, recent studies have indicated the significance of SEs‐associated genes as potential therapeutic targets for several cancers 13,14 . Although increasing evidence suggested that SEs play critical roles in the development of a broad range of cancers, 12,15–17 the functional characterization and clinical significance of SEs in LUAD have not been comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%